5-Bromospiro[1,2-dioxane-4,4 `-tricyclo[4.3.1.1(3,8)]undecane]-3 `-ol - Robinson, T.V.; Taylor, D.K.; Tiekink, Edward R.T. (International Union of Crystallography, 2010)
The title compound, C14H21BrO3, comprises a seven-(C-7) and three six-membered (1 x O2C4 and 2 x C-6) rings, and each adopts a conformation based on a chair. Stability to the molecular structure is afforded by an intramolecular O-H center dot center dot center dot Br hydrogen bond. In the crystal structure, molecules are arranged into a helical supramolecular chain along the b axis, linked by C-H center dot center dot center dot O interactions, where the O-atom acceptor is one of the dioxane O atoms. The crystal studied was found to be a racemic twin. The major component was present 94% of the time.